System y+ arginine transport and NO production in peripheral blood mononuclear cells in pregnancy and preeclampsia. - McCord, N; Ayuk, P; McMahon, M; Boyd, R; Sargent, I; Redman, C (2006)
Systemic inflammation and oxidative stress are features of normal pregnancy and, in excess, contribute to the pathogenesis of preeclampsia. Inflammatory cell activation stimulates uptake of arginine (the precursor for nitric oxide) by transport system y+, expression of one of its genes (CAT-2) together with inducible nitric oxide synthase, leading to nitric oxide production. We investigated whether these changes occur in peripheral blood mononuclear cells in normal pregnancy and are exaggerated in preeclampsia. Samples from matched trios of nonpregnant, normal pregnant, and preeclamptic women were studied. Arginine transport was characterized, and the expression of inducible nitric oxide synthase and cell-specific nitric oxide production were measured. Arginine uptake by system y+ was significantly increased (P<0.001) in peripheral blood mononuclear cells in normal pregnancy but not in preeclampsia. CAT-2 mRNA was not detected in cells from nonpregnant women but was detected in 3 of 10 normal pregnant and 8 of 10 of preeclamptic women (P<0.001). Inducible nitric oxide synthase protein expression was significantly increased in normal pregnant women (P<0.05) but not preeclamptic women. No significant differences in cell-specific nitric oxide production were observed. These changes confirm the predictions for normal pregnancy but not for preeclampsia in which, despite increases in CAT-2 expression, arginine uptake is not additionally increased. This may create a relative deficiency of arginine in PBMCs favoring superoxide and peroxynitrite production and contribute to oxidative and nitrosative stress in preeclampsia.